2021
DOI: 10.1007/s11481-021-09982-7
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory Potential of Cannabidiol in Multiple Sclerosis: a Systematic Review

Abstract: Multiple sclerosis (MS) is the most common chronic autoimmune disease of the central nervous system. Efficacy of treatments for MS is associated with risk of adverse effects, and effective and well-tolerated drugs remain a major unmet need. Cannabis (Cannabis sativa L., fam. Cannabaceae) and cannabinoids are popular among MS patients to treat spasticity and pain. Cannabinoids are endowed with remarkable immunomodulating properties, and in particular the non-psychotropic cannabinoid cannabidiol (CBD) is increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
33
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 87 publications
(148 reference statements)
2
33
0
Order By: Relevance
“…Moreover, the high impact of MDSCs in CBD-mediated attenuation of EAE led to the inhibition of myelin oligodendrocyte glycoprotein (MOG)-induced proliferation of T cells in vitro . Thereby, the studies confirmed that by inducing immunosuppressive MDSCs, CBD-based treatment may minimize EAR [ 47 , 77 ]. Besides the results obtained in rodent models of EAE that showed efficient action of CBD, more tests and clinical trials are needed to identify the action of CBD in human immune cells [ 47 ].…”
Section: Recent Developments On the Molecular Mechanism Of Action Of Cbd For Multiple Sclerosis (Ms)mentioning
confidence: 79%
See 4 more Smart Citations
“…Moreover, the high impact of MDSCs in CBD-mediated attenuation of EAE led to the inhibition of myelin oligodendrocyte glycoprotein (MOG)-induced proliferation of T cells in vitro . Thereby, the studies confirmed that by inducing immunosuppressive MDSCs, CBD-based treatment may minimize EAR [ 47 , 77 ]. Besides the results obtained in rodent models of EAE that showed efficient action of CBD, more tests and clinical trials are needed to identify the action of CBD in human immune cells [ 47 ].…”
Section: Recent Developments On the Molecular Mechanism Of Action Of Cbd For Multiple Sclerosis (Ms)mentioning
confidence: 79%
“…This process can clarify the lower risk of developing psychotic symptoms in patients who use preparations based on high ∆ 9 -THC and CBD ratios in comparison If conventional antispastic therapy is not efficient enough, then nabiximols, commercially known as Sativex (containing CBD and THC) were mainly recommended for the treatment of pain and spasticity in MS [72], but can also be applied in inflammatory disease therapy with demyelination and neuronal injury in the brain and spinal cord. For the treatment of spasticity, Sativex was approved for the first time by the UK in 2010; however, nowadays it is recommended in more than 25 countries [47]. Interestingly, recent reports showed that the use of Cannabis is reported by 20-60% of patients with MS [47].…”
Section: Antioxidant Properties Of Cbdmentioning
confidence: 99%
See 3 more Smart Citations